90.6k views
3 votes
I need help checking to make sure my work is correct. Start with the basic function f(x) = 2x. If you have an initial value of 1, then you end up with the following iterations:f(1) = 2 x 1 = 2f^2 (1) = 2 x 2 x 1 = 4f^3 (1) = 2 x 2 x 2 x 1 = 8The question Part 1: If you continue the pattern, what do you expect would happen to the numbers as the number of iterations grows? Check your result by conducting at least 10 iterations. I put: f^4 (1) = 2 x 2 x 2 x 2 x 1 = 16f^5 (1) = 2 x 2 x 2 x 2 x 2 x 1 = 32f^6 (1) = 2 x 2 x 2 x 2 x 2 x 2 x 1 = 64f^7 (1) = 2 x 2 x 2 x 2 x 2 x 2 x 2 x 1 = 128f^8 (1) = 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 1 = 256f^9 (1) = 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 1 = 512f^10 (1) = 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 2 x 1 = 1024Part 2: Repeat the process with an initial value of -1. What happens as the number of iterations grows?

User Jed Grant
by
4.7k points

1 Answer

0 votes

Given: The function below:


f(x)=2x

To Determine: The interation with initial value of 1

When the initial value is 1, it means that x = 1

If x =1, we can determine f(1) by the substituting for x in the function as shown below:


\begin{gathered} f(x)=2x \\ x=1 \\ f(1)=2(1)=2*1=2 \end{gathered}
f^2(1)=2^2*1=2*2*1=4

Part 1:

It can be observed that as the number of iterations grow, the number increase in powers of 2

This can be modelled as


f^n=2^n*1=2^n
f^(10)=2^(10)*1=1024

Part 2:

If we repeat the process with an initial value of -1. As the number of iterations grows, the number can be modelled as


\begin{gathered} f^(-n)=2^(-n)*1 \\ f^(-1)=2^(-1)*1=(1)/(2)*1=(1)/(2) \\ \text{For initial value of -2, we would have} \\ f^(-2)=2^(-2)*1=(1)/(2^2)*1=(1)/(4) \end{gathered}

So, as the initial value decreases, it can be observed by the above calculations that the number would be decreasing by the the reciprocal of the power of 2.

User Bei
by
4.6k points